2004
DOI: 10.3168/jds.s0022-0302(04)73240-3
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Tissue Mass and Rumen Volume in Dairy Cows During the Transition from Late Gestation to Early Lactation

Abstract: The objectives were to measure the effects of transition and supplemental barley or rumen-protected protein on visceral tissue mass in dairy cows and the effects of transition and barley on rumen volume and liquid turnover. Cows were individually fed a grass silage-based gestation ration to meet energy and protein requirements for body weight stasis beginning 6 wk before expected calving. A corn silage-based lactation ration was individually fed ad libitum after calving. In the visceral mass study, 36 cows wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
90
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 29 publications
19
90
2
2
Order By: Relevance
“…This is also demonstrated by infusion of glucose into the jejunum of rats, which stimulated mucosal protein synthesis (Weber et al, 1989). Reynolds et al (2004) found that changes in gastro-intestinal and liver mass during transition are apparently consequences of changes in DMI and nutrient supply and not initiated by lactation per se. They also found that the type of diet had little effect on visceral mass.…”
Section: Discussionmentioning
confidence: 94%
“…This is also demonstrated by infusion of glucose into the jejunum of rats, which stimulated mucosal protein synthesis (Weber et al, 1989). Reynolds et al (2004) found that changes in gastro-intestinal and liver mass during transition are apparently consequences of changes in DMI and nutrient supply and not initiated by lactation per se. They also found that the type of diet had little effect on visceral mass.…”
Section: Discussionmentioning
confidence: 94%
“…The extent to which the EAAs taken up by the liver were actually utilised for gluconeogenesis is in fact unknown and would require use of isotope tracer studies, as conducted for some non-EAAs by Bergman and Heitmann (1978). Taking the numerous metabolic pathways utilising EAAs for anabolic purposes, for example, synthesis of export proteins (Bender, 1985) and post partum liver growth (Gibb et al, 1992;Reynolds et al, 2004), these would likely leave very little EAAs for gluconeogenesis on a net basis.…”
Section: Quantitative Measurementsmentioning
confidence: 99%
“…A) Anatomical development -It is the growth of rumen mass and rumen papillae (Reynolds et al, 2004). Rumen Papillae are finger-like projections present on the surface of the rumen, which absorb nutrients from the rumen contents, and for its development, rumen microbes require moisture, a fermentable substance, and heat (required for fermentation provided by the body temperature of the calf).…”
Section: Development Of the Rumen As An Organmentioning
confidence: 99%